Active management of third stage of labour: comparison between prophylactic intramuscular methylergometrine and intramuscular oxytocin - Adhikari, Shilu; Rana, Ashma; Bista, Kesang D (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Aim: Aimed at comparing the efficacy of prophylactic intramuscular methylergometrine with intramuscular oxytocin in reducing blood loss in the third stage of labour (TSL). Methods: This is a randomized, comparative, clinical trial to compare the efficacy of intramuscular methylergometrine with intramuscular oxytocin in the third stage of labour for the prevention of postpartum hemorrhage Two hundred women undergoing normal vaginal delivery were recruited, 100 in each group- Group A receiving .2mg methylergometrine intramuscularly and Group B receiving 10U oxytocin intramuscularly immediately after the delivery of the anterior shoulder of the baby. The efficacy and the safety of these two drugs were analyzed on the basis of percentages fall in haemoglobin (Hb) and haematocrit (Hct) level from before delivery to 24 completed hours after delivery, need for additional uterotonic agents, need for exploration and uterine evacuation, need for blood transfusion, duration of third stage of labour and the numbers of retained placenta and need for MRP. Results: Intramuscular methylergometrine was observed to be equally effective as intramuscular oxytocin in prevention of post partum haemorrhage (PPH) [defined as fall in Hb and /or Hct level³ 10% from before delivery to 24 hours after delivery]. There was no difference in the risk of prolonged third stage, need for additional uterotonic agents, need for exploration and uterine evacuation and need for blood transfusion in the two groups. The side effects were all mild in nature and the overall incidence was too low for statistical significance to be elicited. Conclusion: Intramuscular methylergometrine is as efficacious as intramuscular oxytocin in the prevention of third stage blood loss with comparable side effects. Keywords: Third stage of labour, postpartum hemorrhage, methylergometrine, oxytocin. doi:10.3126/njog.v2i2.1451 N. J. Obstet. Gynaecol 2007 Nov-Dec; 2 (2): 24 - 28